Cultural Humility for People of Color Critique of Current Theory and Practice - Moon, Sarah H.; Sandage, Steven J. 1967- (2019)
Cultural humility and the broader multicultural orientation approach (MCO) is important for clinicians of color as it is for White clinicians; however, the MCO framework does not address how experiences of racism and oppression impact how therapists of color think about and practice cultural humility. This article attempts to address important ways that the dialogue around cultural humility must be nuanced for therapists of color, and will provide examples of ways in which the framework for racial/ethnic minority community is fundamentally unique, both conceptually and in application: perspectives will be provided through responding to concepts within MCO framework such as "other-oriented" stance, leaning into cultural opportunities, and cultural comfort from a person-of-color lens. We contend that the traumatic effects of racism, microaggression, intergenerational trauma, and the pressures to assimilate to White culture make it difficult for therapists to practice cultural humility in the way that it is currently discussed in the literature. The authors provide potential resources for therapists of color, and explore how it is essential to have institutional and communal resources provided in White spaces.
Keywords: cultural humility; Ethnicity; Psychology; Race; Racism